2013
DOI: 10.1088/0004-637x/770/1/61
|View full text |Cite
|
Sign up to set email alerts
|

The Imacs Cluster Building Survey. I. Description of the Survey and Analysis Methods

Abstract: The IMACS Cluster Building Survey uses the wide field spectroscopic capabilities of the IMACS spectrograph on the 6.5m Baade Telescope to survey the large-scale environment surrounding rich intermediate-redshift clusters of galaxies. The goal is to understand the processes which may be transforming star-forming field galaxies into quiescent cluster members as groups and individual galaxies fall into the cluster from the surrounding supercluster. This first paper describes the survey: the data taking and reduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…The second assumption is a bit more complex. In a recent study of galaxy clusters at z ∼ 0.3−0.5, Oemler et al (2013) found little difference between the strength of the EW(Hδ) and EW([OII]) for galaxies in their sample when slit apertures of two different sizes were used. The covering fraction of these two slit sizes was disparate enough for them to conclude that a spectrum observed with a 1 slit is sufficiently representative of the galaxy as a whole for a large fraction of their sample.…”
Section: A/k Ratios and Continuum Measurementsmentioning
confidence: 96%
See 2 more Smart Citations
“…The second assumption is a bit more complex. In a recent study of galaxy clusters at z ∼ 0.3−0.5, Oemler et al (2013) found little difference between the strength of the EW(Hδ) and EW([OII]) for galaxies in their sample when slit apertures of two different sizes were used. The covering fraction of these two slit sizes was disparate enough for them to conclude that a spectrum observed with a 1 slit is sufficiently representative of the galaxy as a whole for a large fraction of their sample.…”
Section: A/k Ratios and Continuum Measurementsmentioning
confidence: 96%
“…The covering fraction of these two slit sizes was disparate enough for them to conclude that a spectrum observed with a 1 slit is sufficiently representative of the galaxy as a whole for a large fraction of their sample. The sample we consider here is bounded on the low-redshift end by the high-redshift galaxies in the sample of Oemler et al (2013). As such, the covering fraction for the galaxies in our sample, given that the VVDS galaxies were observed with a 1 , is equivalent or higher than that of Oemler et al (2013) and approaches unity at z > ∼ 1.…”
Section: A/k Ratios and Continuum Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying galaxy observations were taken from a number of galaxy surveys. In particular, the stellar masses and SFRs for galaxies with * >´ M M 4 10 10 were drawn from the Sloan Digital Sky Survey (see Oemler et al 2013b, and references therein), whereas the PG2MC survey (Calvi et al 2011) was used for galaxies with * <´ M M 4 10 10 . Due to the smaller volume of the latter survey, the samples were re-normalized to create equal weights.…”
Section: The Gladders Et Al Galaxy Samplementioning
confidence: 99%
“…We can mention: the ESO Distant Cluster Survey (EDisCS, White et al 2005) in a wide range of mass, with redshifts from 0.4 to almost 1.0; the X-ray-luminous clusters from the MACS survey at z ≈ 0.5 within a 1.2 Mpc diameter (Stott et al 2007); the Observations of Redshift Evolution in Large-Scale Environments (ORELSE) Survey (Lubin et al 2009), a systematic search for structure around well-known clusters at redshifts of 0.6 < z < 1.3; the galaxy populations in the core of a massive, X-ray luminous cluster (Strazzullo et al 2010) at z=1.39; and the IMACS Cluster Building Survey (Oemler et al 2013) to understand the large-scale environment surrounding rich intermediate redshift clusters of galaxies.…”
Section: Introductionmentioning
confidence: 99%